Reporters of history: gamification within the framework of an interdisciplinary project in a multigrade classroom of primary school - Callarisa Mas, Joan; Guinó Arias, Margarita (Clio. History and History Teaching, 2022)
This article describes the development of a collaborative project shared both by school and university. In this case, between the University of Vic and the Pompeu Fabra School of Salt. In this project the main role is played by the students of the third cycle of primary school of the Pompeu Fabra School of Salt (Gironès) and a group of thirteen students of the University of Vic enrolled in the subject Didactics of Social Sciences, from the double degree in Early Childhood and Primary Education Teacher in English. This collaboration has been structured around the participation of the primary school group in the interdisciplinary project "Reporters of History".
Keywords: projects; collaboration; cultures in the Middle Age; Didactics; Methodologies; Teaching-learning Social Sciencies